Antimicrobial resistance and genotyping of Salmonella Typhimurium strains isolated from guinea pigs (Cavia porcellus) from intensive production farms of the city of Lima, Peru - Salvatierra R., Guillermo (2018)
The aim of this study was to characterize 20 strains of Salmonella enterica at molecular level and antimicrobial resistance. Of these, 15 strains were obtained from infected guinea pigs and five from clinically healthy guinea pigs from two intensive production centers located in Lima, Peru. The invA, prot6E and fliC genes corresponding to the genus Salmonella and serovars Enteritidis and Typhimurium, respectively, were detected by a multiple PCR technique. Genetic variability was detected using the BOX-PCR technique using the first BOXA1R. Resistance was evaluated using the Kirby Bauer technique based on erythromycin, nitrofurantoin, streptomycin, penicillin, enrofloxacin, fosfomycin, amoxicillin with clavulanic acid, sulfatrimetoprim and ciprofloxacin. Serotype Typhimurium was determined in 100% of the isolates. The evaluation of the electrophoretic profiles obtained by the BOX-PCR technique demonstrated high homogeneity, with similar DNA bands patterns. Strains resistant to erythromycin 60% (12/20), nitrofurantoin 40% (8/20), streptomycin 30% (6/20), penicillin 25% (5/20), and enrofloxacin 10% (2/20) were detected. The detection of resistant strains may cause problems in the treatment of salmonellosis in guinea pigs and the presence of only a genetic group suggests a clonal dispersion.